2020
DOI: 10.3390/toxins12080516
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing and Toxin Production in Staphylococcus aureus Osteomyelitis: Pathogenesis and Paradox

Abstract: Staphylococcus aureus is a Gram-positive pathogen capable of infecting nearly every vertebrate organ. Among these tissues, invasive infection of bone (osteomyelitis) is particularly common and induces high morbidity. Treatment of osteomyelitis is notoriously difficult and often requires debridement of diseased bone in conjunction with prolonged antibiotic treatment to resolve infection. During osteomyelitis, S. aureus forms characteristic multicellular microcolonies in distinct niches within bone. Virulence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 161 publications
(254 reference statements)
2
40
0
Order By: Relevance
“…Key characteristics of osteomyelitis are severe inflammation, vascular impairment, and localized bone loss and destruction (2). The host responds to the presence of bacteria such as S. aureus by releasing inflammatory factors and degradative enzymes from immune cells, which contribute to the destruction of bone matrix and bone trabeculae (1,(5)(6)(7)(8)(9)(10). Many of the innate immune responses involved in antibacterial host defense also have significant impacts on bone homeostasis, and the release of inflammatory mediators at the infection site can result in decreased osteoblast-mediated bone formation and increased osteoclast activation and bone resorption, thereby promoting bone loss.…”
Section: The Development Of Chronic Osteomyelitismentioning
confidence: 99%
“…Key characteristics of osteomyelitis are severe inflammation, vascular impairment, and localized bone loss and destruction (2). The host responds to the presence of bacteria such as S. aureus by releasing inflammatory factors and degradative enzymes from immune cells, which contribute to the destruction of bone matrix and bone trabeculae (1,(5)(6)(7)(8)(9)(10). Many of the innate immune responses involved in antibacterial host defense also have significant impacts on bone homeostasis, and the release of inflammatory mediators at the infection site can result in decreased osteoblast-mediated bone formation and increased osteoclast activation and bone resorption, thereby promoting bone loss.…”
Section: The Development Of Chronic Osteomyelitismentioning
confidence: 99%
“…In S. aureus, the agr quorum sensing system plays a major role in the regulation of virulence factors production [10]. The agr operon consists of four genes: agrB, agrD, agrC, and agrA.…”
Section: Discussionmentioning
confidence: 99%
“…RNAIII serves to enhance the expression of genes encoding toxins, such as α-hemolysin, while reducing the expression of genes encoding surface proteins. Although most of the QS regulation depends on RNAIII, it has been shown that AgrA, upon phosphorylation, is also directly responsible for the production of some virulence factors, such as phenol-soluble modulines (PSMs) [10]. It is believed that the agr system influences biofilms in vivo by upregulating PSMs expression, which are involved in the structure of biofilms by forming channels and promoting cell dispersal from the biofilm to further colonize the host [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors described a decrease in virulence and toxin genes that most likely reflect the bacterial adaptation process towards a persisting phenotype [ 34 ]. Additionally, in S. aureus osteomyelitis, the bacteria revealed adaptation strategies largely controlled by the accessory gene regulator ( agr ) locus, which is extensively reviewed by Butrico et al [ 35 ]. Finally, Wong Fok Lung et al display the S. aureus metabolic adaptation that is induced by the host immune response and results in bacterial strains adapted for chronicity [ 36 ].…”
mentioning
confidence: 99%